One-Step Synthesis of Mesoporous Silica Thin Films Containing Available COOH Groups - Escobar, Ane (ACS Omega, 2017)
[Image: see text] Inorganic–organic hybrid mesoporous silica thin films with covalently bonded carboxylic acid groups were synthesized in a one-step procedure, using carboxylic-derivatized alkoxysilanes obtained by photochemical radical thiol-ene addition (PRTEA). The organosilanes were synthesized by clicking mercaptosuccinic or mercaptoacetic thioacids with vinyltrimethoxysilane, using benzophenone as the photoradical initiator. The films were synthesized by evaporation-induced self-assembly of a sol containing a mixture of tetraethoxysilane and different quantities of the organosilanes, without any further treatment after the PRTEA reaction. Two nonionic surfactants were used as templates to produce different pore sizes. Different aging times were also applied. Structural characterization with electron microscopy, porosimetry measurements, and small angle X-ray scattering with two-dimensional detection demonstrated the obtention of mesoporous phases whose degree of ordering depended on the amount of added organosilane. The incorporation of the functional silanes was shown by X-ray photoelectron spectroscopy, and the presence of the COOH groups was confirmed by Fourier transform infrared (FTIR). Finally, the availability of the COOH groups for further chemical modification was demonstrated by FTIR by following the changes in the typical carbonyl IR bands during proton exchange and metal complexation. The proposed simple methodology allows obtaining COOH-modified silica thin films in one step, without the need of hard reaction conditions or deprotection steps. Functionalization with carboxyl groups brings a pH-dependent switch-ability to the pore surface that can be used for multifunctional mesoporous materials design.